53 Piloting patch – providing assessment and treatment for children at home – and piecing together what works. Issue 12 (23rd November 2017) - Ward, Caroline; Knight, Katie; Ballard, Mary-Rose; Keogh, Georgina; Samuel, Miriam; Buttle, Sara; Robb, Claire; Cleugh, Francesca
Abstract : Aims: PATCH is a pilot acute community children's nurse led service delivering assessment and treatment for children at home who are moderately unwell and might otherwise be admitted to hospital or attend Paediatric Emergency Department (PED). Children are referred by PED or GP and followed up via telephone support and home visits depending on clinical need for duration of acute illness. Methods: Pilot year funded by Imperial Charity. Using evaluation to build business case for sustained commissioned service. Phase 1 Sept 2016 – May 2017 : reduced short stay admissions and re-attendances to PED for common mild-moderate respiratory conditions e.g., viral wheeze, bronchiolitis. Phase 2 from May 2017 : piloting direct GP referrals to PATCH team to evaluate impact in reducing attendances to PED for children needing further assessment or support beyond GP consultation, and enabling families to manage common acute conditions at home. Using QI methodology, Model for Improvement we developed a driver diagram and used real-time PDSA cycles to capture our learning and inform small iterative changes of service development. Process mapping and world cafe style events were held with local community nurses, health visitor leads, GPs and commissioners to co-design referral pathways and explore more widely how PATCH fits into the whole urgent care system. Parental feedback evaluated via semi structured interviews. Results: Activity – Appendix 1 Phase 1 – Concentrated on respiratory conditions from PED. Total 188 referrals in first 7 months. Bronchiolitis 45%; viral wheeze 37.5%; asthma 7%; lower respiratory tract infections 5.4%. 50% of patients received home visits and telephone consultations; 50% only telephone support. Successes: Cost effective – Appendix 2 73 acute admissions avoided, costing c£400 per/night 97 PED re-attendances prevented at £117 per attendance. Projected cost avoidance within acute care provider £3 27 640 pa. Estimated cost of service £2 84 000 pa. Positive feedback and reported health seeking behaviour change – Appendix 3 Challenges: Information governance, cross organisational working, complex commissioning arrangements. Discussion: Within first 7 months PATCH has had a significant impact on avoiding admissions and re-attendances, thus improving flow and performance in PED. The projected financial impact is that it is cost effective. We are using this data to pursue a business case internally and with local CCGs. We are optimistic of succeeding and using phase 2 to build on partnerships garnered across the whole system to expand PATCH's impact further by reducing PED attendances and continuing to improve our local urgent care pathway for children.